Fast and scalable image retrieval using predictive clustering trees - Dimitrovski, Ivica; Kocev, Dragi; Loshkovska, Suzana; Džeroski, Sasho (Springer, Berlin, Heidelberg, 2013)
The recent overwhelming increase in the amount of available visual information, especially digital images,has brought up a pressing need to develop efficient and accurate systems for image retrieval. Stateof-the-art systems for image retrieval use the bag-of-visual-words representation of the images. However, the computational bottleneck in all such systems is the construction of the visual vocabulary (i.e., how to obtain the visual words). This is typically performed by clustering hundreds of thousands or millions of local descriptors, where the resulting clusters correspond to visual words. Each image is then represented by a histogram of the distribution of its local descriptors throughout the vocabulary. The major issue in the retrieval systems is that by increasing the sizes of the image databases, the number of local descriptors to be clustered increases rapidly: Thus, using conventional clustering techniques is infeasible. Considering this, we propose to construct the visual codebook by using predictive clustering trees, which are very efficient and have good performance. Moreover, to increase the stability of the model, we propose to use random forests of predictive clustering trees. We evaluate the proposed method on a benchmark database of a million images and compare it to other state-of-the-art methods. The results reveal that the proposed method produces a visual vocabulary with superior discriminative power and thus better retrieval performance.
Keywords: image retrieval, visual vocabulary construction, predictive clustering